Case report of a pituitary thyrotropin-secreting macroadenoma with Hashimoto thyroiditis and infertility. Issue 1 (January 2018) - Li, Jiaqi; Li, Jianwei; Jiang, Shu; Yu, Ruichao; Yu, Yerong
Abstract: Rationale: Thyrotropin-secreting adenoma (TSHoma) is rare, diagnosis and treatment are often delayed if the condition coexists with Hashimoto thyroiditis. The enlarged pituitary adenoma may eventually induce panhypopituitarism, infertility, or the compression of optic nerves and optic chiasma. Patient concerns: This patient was a 36-year-old man who had been referred to the pituitary disease multidisciplinary team (MDT) of the West China Hospital, due to infertility. Diagnoses: Examinations revealed pituitary thyrotropin-secreting macroadenoma. Interventions: We conducted trans-sphenoidal surgery. Human chorionic gonadotropin (HCG) and human menopausal gonadotropin (HMG) were used for reproductive reconstruction after surgery. Outcomes: This patient successfully fathered a child. Lessons: To date, the multidisciplinary team treatment of TSHoma was rare, TSHomas are often misdiagnosed as macroadenomas, because the clinical features are varied and it often takes a long time to be diagnosed. So the purpose of this case report is to attract attention to the manifestation of increased thyroid stimulating hormone (TSH) concentration and discuss MDT treatment for TSH-secreting adenoma.